AUDIT SISTEM INFORMASI APLIKASI M-PASPOR MENGGUNAKAN FRAMEWORK COBIT 5 DI DIREKTORAT JENDERAL IMIGRASI - Indah Purnamasari; Noval Noval (Universitas Dharmawangsa, 2025)
The M-Paspor application is an information technology-based service designed to simplify the passport application process online. However, in its implementation, the application still faces several issues, such as network disruptions, user difficulties, quota limitations, and technical problems that hinder service effectiveness. Furthermore, the absence of an information system governance audit based on the COBIT 5 framework has resulted in suboptimal IT processes that do not fully support the organization's vision and mission. This study aims to evaluate the performance of the M-Paspor application to ensure it operates in alignment with organizational objectives through a COBIT 5-based audit. The research employs a quantitative method, using data collection techniques such as observation, interviews, and questionnaires involving relevant stakeholders. The COBIT 5 framework is applied to analyze IT governance and management domains, enabling the identification of weaknesses in processes and providing recommendations for improvement. The audit results indicate that the M-Paspor application has several areas requiring enhancement, particularly in technical reliability, user experience, and network risk mitigation. The implementation of COBIT 5 provides a structured guide to improving the efficiency and effectiveness of information systems while aligning IT processes with the organization's strategic objectives. Thus, a COBIT 5-based audit is an effective solution for improving the quality of the M-Paspor application and supporting organizational performance optimization.